The historiographical significance of K. K. Palen’s inspection reports in the Turkestan region in 1908-1909 - Nodira Sirojovna Nuritdinova (Annals of Justice and Humanity, 2025)
Purpose: This study explores the historical significance of the senatorial inspection led by Count K.K. Palen in Turkestan during 1908–1909. It aims to understand the political, economic, and cultural dynamics of the region under Russian colonial rule and assess how these reports shaped historiography on early 20th-century Central Asia. Research methodology: The research applies a qualitative historical approach through textual and historiographical analysis of Palen’s inspection reports, official records, and contemporary publications. Comparative evaluation was conducted to interpret the collected data in the context of colonial administration and regional transformation. Results: The findings reveal that the inspection exposed widespread corruption and maladministration while simultaneously producing reliable empirical data, including the only comprehensive household survey of dehkan farms in Turkestan before 1917. The reports provide valuable insights into land use, governance structures, and socio-economic changes driven by Russia’s expansionist policies. Conclusions: Palen’s reports serve as a fundamental source for reconstructing the realities of colonial Turkestan. They illustrate the duality of Russia’s civilizing mission and the exploitation of resources, offering both critical evidence of systemic flaws and documentation of modernization processes. Limitations: The inspection materials, while rich, reflect the perspectives of Russian officials and may underrepresent indigenous voices and experiences. Contribution: This study contributes to Central Asian historiography by positioning Palen’s inspection as a unique and comprehensive documentary source for analyzing governance, economic practices, and colonial discourse.